Signs of musculoskeletal disorders in bus drivers and fare collectors - Malú de Oliveira Freire; Aline Rodrigues Barbosa; Lélia Renata das Virgens Carneiro; Raildo da Silva Coqueiro (Universidade Federal de Santa Catarina, 2007)
To describe the signs of musculoskeletal disorders (SMD) in drivers and fare ollectors and to investigate their association with hours worked per day, nutritional status and level of physical activity (PA). A cross-sectional study undertaken with 40 bus drivers and 39 fare collectors working intercity routes. The "Nordic Musculoskeletal Questionnaire" was used to identify SMD. The working day was defi ned according to median values (< 8 hours or ≥ 8 hours). Level of PA was assessed using the short version of the International Physical Activity Questionnaire. Body mass index was used to verify nutritional status. The chi squared test was used to test for associations. Musculoskeletal pain during the previous 12 months was reported by 70.0% and 76.9% of drivers and fare collectors, respectively; 30.0% of the drivers and 33.3% of the fare collectors reported pain during the previous 7 days; 26.6% (drivers) and 33.3% (fare collectors) had had to miss work due to musculoskeletal pain. The highest prevalence rates (previous 12 months) were observed in the following anatomical areas: shoulders (32.5%), for drivers and lower back (48,7%), for fare collectors. There was a signifi cant difference (p = 0.029) between drivers and fare collectors in terms of reported lower back pain. The prevalence of overweight was greater among drivers (72,0%) than fare collectors (33,3%) and this difference was signifi cant (p = 0,000). Signs of musculoskeletal disorders were frequent among the workers and their symptoms did not exhibit any association with the length of working day, nutritional status or level of physical activity. ABSTRACT O objetivo deste estudo foi descrever os sintomas de distúrbios osteomusculares (SDO) em motoristas e cobradores de ônibus e investigar sua associação com jornada de trabalho, estado nutricional e nível de atividade física. Estudo transversal realizado com 40 motoristas e 39 cobradores de ônibus de viagens intermunicipais. Os SDO foram verificados, utilizando-se o Questionário Nórdico de Sintomas Osteomusculares. A jornada de trabalho foi categorizada a partir dos valores da mediana (< 8 horas e ≥ 8 horas). O índice de massa corporal (IMC) foi usado para verificar o estado nutricional. O nível de atividade física foi avaliado, usando-se o Questionário Internacional de Atividade Física (versão curta). As associações foram verifi cadas por teste qui-quadrado. A freqüência de dor em alguma região do corpo (últimos 12 meses) foi de 70,0% e 76,9% para motoristas e cobradores respectivamente; 30,0% dos motoristas e 33,3% dos cobradores referiram dor nos últimos 7 dias; 26,6% e 33,3% dos motoristas e cobradores, respectivamente, tiveram que evitar o trabalho devido às dores. As maiores prevalências (últimos 12 meses) foram observadas nas seguintes regiões anatômicas: ombros (32,5%), para motoristas e; lombar (48,7%), para cobradores. Houve diferença significativa (p = 0,029) entre motoristas e cobradores quanto ao relato de dor na região "lombar". A prevalência de sobrepeso foi maior nos motoristas (72,0%) do que nos cobradores (33,3%), as diferenças foram signifi cativas (p = 0,000). Conclusão - Os SDO foram prevalentes entre os motoristas e cobradores e estes sintomas não mostraram associação com a jornada de trabalho, o estado nutricional e o nível de atividade física.